2017
DOI: 10.1007/s11356-017-0056-5
|View full text |Cite
|
Sign up to set email alerts
|

Does low uranium concentration generates phytotoxic symptoms in Pisum sativum L. in nutrient medium?

Abstract: Due to excessive mining and use of radionuclide especially uranium (U) and its fission products, numerous health hazards as well as environmental contamination worldwide have been created. The present study focused on demonstrating whether low concentration of U treatment in liquid nutient medium may translocate traces of U in plants and in fruits of Pisum sativum after 30 and 60 days of exposure for the safe use as a food supplement for human/animals. Hydroponically grown plants (in amended Hoagland medium) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The link between U and the homeostasis of Ca has been previously reported in several plant species (Vanhoudt et al, 2011b;Tawussi et al, 2017;El Hayek et al, 2018;El Hayek et al, 2019;Rajabi et al, 2021) but no evidence was provided to support the uptake of the radionuclide by the Ca assimilation machinery. In this work, we provide several lines of evidence that U is taken up by the roots of Arabidopsis plants through Ca 2+ -permeable cation channels.…”
Section: Discussionmentioning
confidence: 94%
“…The link between U and the homeostasis of Ca has been previously reported in several plant species (Vanhoudt et al, 2011b;Tawussi et al, 2017;El Hayek et al, 2018;El Hayek et al, 2019;Rajabi et al, 2021) but no evidence was provided to support the uptake of the radionuclide by the Ca assimilation machinery. In this work, we provide several lines of evidence that U is taken up by the roots of Arabidopsis plants through Ca 2+ -permeable cation channels.…”
Section: Discussionmentioning
confidence: 94%
“…In plants, it was also found that U accumulation in plants was directly related to mobile calcium content in soil (Ratnikov et al, 2020). The interference of U with calcium uptake and homeostasis has been also reported in numerous studies (El Hayek et al, 2018;Moll et al, 2020;Rajabi et al, 2021;Straczek et al, 2009;Tawussi et al, 2017;Vanhoudt et al, 2010). The observed increase in cytoplasmic calcium reported in some cases could represent a cellular defense mechanism in response to the presence of U (White and Broadley, 2003).…”
Section: Living Yeast S Cerevisiae Is Able To Accumulate Umentioning
confidence: 62%